Politik Hukum Pembebanan Pajak dalam Perdagangan melalui Sistem Elektronik (PMSE) di Indonesia - Mohammad Hanif Akbar; Sanusi Sanusi; Soesi Idayanti; Moh. Taufik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The 2019 e-commerce survey conducted by the Central Bureau of Statistics (BPS) revealed that many business sectors had begun adopting online sales, accounting for 45.31% of total businesses in Indonesia between 2017 and 2018. During this period, there were 13,485 e-commerce businesses with sales reaching IDR 17.21 trillion from 24.82 million transactions. This growth continued, as the 2023 e-commerce survey estimated that the number of e-commerce businesses in Indonesia reached 2,995,986 in 2022. However, a significant issue remains, as only 20.72% of e-commerce businesses prepare financial reports. This study aims to examine the legal policy of tax imposition on e-commerce transactions, including the challenges and opportunities in implementing e-commerce taxation in Indonesia. This research uses a library research method with an empirical juridical approach and qualitative analysis of taxation policies related to e-commerce transactions. Tax collection is based on legal provisions, as stated in Article 23A of the 1945 Constitution of the Republic of Indonesia, which regulates taxes and other compulsory state charges through laws. The Directorate General of Taxes circular refers to guidelines issued by the Organization for Economic Co-operation and Development (OECD) regarding electronic commerce.